Characterizing saline uptake and salt distributions in porous limestone with neutron radiography and X-ray micro-tomography. (April 2013) - Derluyn, Hannelore; Griffa, Michele; Mannes, David; Jerjen, Iwan; Dewanckele, Jan; Vontobel, Peter; Sheppard, Adrian; Derome, Dominique; Cnudde, Veerle; Lehmann, Eberhard; Carmeliet, Jan
Samples of Savonnières limestone subjected to repeated wetting–drying cycles were investigated by both neutron radiography and X-ray micro-tomography to collect information on saline uptake and salt precipitation. Capillary uptake of water, 1.4 molal sodium sulphate and 5.8 molal sodium chloride solution was visualized with neutron radiography. The liquid penetration coefficients and diffusivities were determined and are markedly lower for the salt solutions than for water, due to the higher surface tension and viscosity of salt solutions. Halite distributions were derived from neutron radiographs. Porosity analysis of X-ray tomographic datasets allowed quantifying thenardite distributions and porosity decrease due to salt crystallization.